Les textes littéraires et l’enseignement de la phonétique du français à l’université - Gajos, Mieczysław (2023)
The article aims to present the results of a diagnostic study of textbooks for teaching corrective phonetics at the university level. The subjects of the study were literary texts appearing in textbooks for teaching French phonetics. The comparative study covered textbooks published in France and Poland in the years 1971-2010. As a result of the conducted research, the following questions were answered: Are literary texts used in phonetics textbooks? What genres and types of literary texts are used in phonetics textbooks? Which authors are used in phonetics textbooks? What are the texts that are most often the subject of didactic studies? What are literary texts used for in phonetics textbooks?
Keywords: corrective phonetics; phonological competence; French; literature; manual